Pengujian Kualitas Website Kelurahan Rimba Sekampung Berdasarkan Standar Iso 29119:2022 - Muhammad Siddiq; Muhammad Asep Subandri (STIKes Ibnu Sina Ajibarang, 2025)
Government websites must meet high quality standards to ensure optimal functionality, reliability, and security for users. This study aims to test the quality of the Rimba Sekampung Village website based on ISO 29119:2022 standards. Testing is carried out using a variety of methods, including functional, non-functional, usability, and compatibility testing. The data was collected through a series of trials using tools such as Selenium IDE and Apache JMeter. The test results show that this website has a functional test success rate of 97% and an overall feasibility rate of 88.30%. Although most of the features have been tested well, there are some aspects that still need improvement, such as the scope of testing against the needs or features that only reach 56%. This study emphasizes the importance of standard-based testing in improving the quality of website-based digital services at the consumer sector level.